Answer:
x = 3 /17
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
x + x/ 3 = x + 1 /5
x + x /3 = 1 /5 x + 1/ 5 (Distribute)
x + 1 /3 x = 1 /5 x + 1 /5
(x + 1 /3 x) = 1/ 5 x + 1 /5 (Combine Like Terms)
4 /3 x = 1 /5 x + 1 /5
4 /3 x = 1/ 5 x + 1/ 5
Step 2: Subtract 1/5x from both sides.
4 /3 x − 1/ 5 x = 1 /5 x + 1/ 5 − 1 /5 x
17 /15 x = 1 /5
Step 3: Multiply both sides by 15/17.
( 15 /17 ) * ( 17 /15 x) = ( 15 /17 ) * ( 1 /5 )
Which then leaves us with 3/17
Hope this helps!